Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnut.2021.603816
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Response of Sheep and Cow Milk on Acute Digestive Comfort and Lactose Malabsorption: A Randomized Controlled Trial in Female Dairy Avoiders

Abstract: Background: Sheep milk (SM) is a possible alternate dairy source for those who experience digestive symptoms with cow milk (CM). While both the milks contain lactose, one of the causes for self-reported intolerance to CM, the composition of SM and CM also differs across proteins and fats, which have been shown to impact digestive processes.Objective: To compare the acute digestive comfort and lactose malabsorption of SM to CM in female dairy avoiders.Method: In a double-blinded, randomized cross over trial, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
2
12
0
Order By: Relevance
“…However, there are differences between the two milk types: for example SM proteins are more digestible than CM proteins, and provides a greater quantity of branched-chain amino acids (BCAAs) with a corresponding elevation of the postprandial circulating BCAA response ( 15 ). Despite a higher energy and nutrient content in SM, SM did not increase adverse digestive symptoms relative to CM, and reduced the breath H 2 response in dairy-avoiding females, as reported previously ( 16 ). Compared to CM, SM has higher proportions (14.5–27.6 vs. 10.7–16.8%) of short- and medium-chain fatty acids (SCFA; MCFA) ( 17 19 ).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, there are differences between the two milk types: for example SM proteins are more digestible than CM proteins, and provides a greater quantity of branched-chain amino acids (BCAAs) with a corresponding elevation of the postprandial circulating BCAA response ( 15 ). Despite a higher energy and nutrient content in SM, SM did not increase adverse digestive symptoms relative to CM, and reduced the breath H 2 response in dairy-avoiding females, as reported previously ( 16 ). Compared to CM, SM has higher proportions (14.5–27.6 vs. 10.7–16.8%) of short- and medium-chain fatty acids (SCFA; MCFA) ( 17 19 ).…”
Section: Introductionsupporting
confidence: 85%
“…The primary outcome of the study has been reported by Milan et al ( 15 ). Secondary outcomes of lactose malabsorption and digestive comfort have also been reported by Shrestha et al ( 16 ). The additional secondary outcome of lipid responses was assessed and is reported here.…”
Section: Methodssupporting
confidence: 62%
“…It is additionally rich in magnesium and zinc, as well as in B vitamins and vitamins A, E, and C [ 5 ]. Shrestha et al [ 6 ] showed that sheep’s milk, despite its higher energy and nutrient content, does not lead to significant undesirable digestive symptoms to the same extent as cow’s milk. Due to its favorable physical, chemical, and nutritional properties, it can serve as a valuable raw material for the production of fermented beverages, which are the basis of the functional food market [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the disaccharide lactose in milk is commonly assigned to these dairy restrictions due to a health status known as lactose malabsorption (Shrestha et al, 2021). There are some reasons for the manifestation of lactose malabsorption (such as celiac disease, microbial infections, or malnutrition that damages the intestinal villi), but the main one is the lactase nonpersistence (LNP) (OMIM#223100), a phenotypic enzyme deficiency that affects different cultures (EFSA, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, full dairy avoidance from the diet may enhance the risk of nutrient insufficiency and thus contribute to metabolic bone disease, low bone mineral density, or metabolic syndromes (Appleby et al., 2007; Pearlman & Akpotaire, 2019). The presence of the disaccharide lactose in milk is commonly assigned to these dairy restrictions due to a health status known as lactose malabsorption (Shrestha et al., 2021). There are some reasons for the manifestation of lactose malabsorption (such as celiac disease, microbial infections, or malnutrition that damages the intestinal villi), but the main one is the lactase nonpersistence (LNP) (OMIM#223100), a phenotypic enzyme deficiency that affects different cultures (EFSA, 2010).…”
Section: Introductionmentioning
confidence: 99%